Possibility of Harmonization Between Science and Metaphysics in Philosophy - Roqnuzzaman, Md (Philosophy and Progress, 2021)
In respect of the sustainability of humankind on the present-day super motorized overwhelming Earth, harmonization between science and metaphysics becomes an ardent issue for current philosophical quests. On this topic, the underlying problem is, whether or not science and metaphysics could stay harmonically in a single system of knowledge. Science generally deals with necessary truths that inevitably connect sense experience, and conversely, metaphysics deals with super sensory aspects. So, there is a complication of compatibility between them. In this paper, it is expected to show that the harmonious co-existence of science and metaphysics is possible under the contemporary context of epistemological relativity, and this harmony is crucial for the furtherance of humankind on Earth. Philosophy and Progress, Vol#65-66-; No#1-2; Jan-Dec 2019 P 163-178